Fulfillment of Children's Support After Parental Divorce - Gumanti, Vidya; B, Sumiyati; Marwan, Marwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Etymologically, livelihood means something that circulates because it is shared or given to people and makes the life of the person who gets it run smoothly. Because it is shared or given, the livelihood is physically used up or lost from its owner. This research is motivated by the negligence of a father regarding his obligation to provide support for his children after a divorce. Divorce does not result in the loss of a father's obligation to provide support for his children. The problem of this research is how to fulfill child support after divorce. The method used is normative-empirical legal research. Normative-empirical legal research is a research method which in this case combines normative legal elements which are then supported by the addition of data or empirical elements. The research results show that in implementing the obligation to provide support for children after a divorce, a father is negligent in carrying out his obligation to provide support for his children.